Synthesis of five-membered heterocycles by indirect electrochemical approach in "Green" media - Duraes, C. (2015)
Radical cyclization continues to be a central methodology for the preparation of natural products containing heterocyclic rings. Hence, some electrochemical results obtained by cyclic voltammetry and controlled-potential electrolysis in the study of electroreductive intramolecular cyclization of ethyl (2S, 3R)-2-bromo-3-propargyloxy-3-(2’,3’,4’,6’-tetra-O-acetyl-beta-D-glucopyranosyloxy) propanoate (1a), 2-bromo-3-allyloxy-3-(2’,3’,4’,6’-tetra-O-acetyl-beta-D-glucopyranosyloxy)propanoate (1b), 2-bromo-[1-(prop-2-yn-1-yloxy)propyl]benzene (1c) and [1-bromo-2-methoxy-2-(prop-2’-yn-1-yloxy)ethyl]benzene (1d) promoted by (1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane)nickel(I), [Ni(tmc)]+, electrogenerated at glassy carbon cathodes in ethanol and ethanol:water mixtures containing tetraalkylammonium salts, are presented. During controlled-potential electrolyses of solutions containing [Ni(tmc)]2+ and bromoalkoxylated compounds (1) catalytic reduction of the latter proceeds via one-electron cleavage of the carbon–bromine bond to form a radical intermediate that undergoes cyclization to afford the substituted tetrahydrofurans.